Comparative analysis of wetland dynamics, vulnerability and resilience in the Mekong and Yellow River Deltas - Yaseen Laghari; Zhenguo Niu; Shah Jahan Leghari; Muhammad Asgher Ali; Qingyu Li; Junkai Shi; Xiaonan Zhou; Li Wang (Estuarine, Coastal and Shelf Science, 2026)

Retraction notice to “Environmentally responsive and anti-bugs textile finishes – Recent trends, challenges, and future perspectives” [Sci. Total Environ. 690 (2019) 667–682] - Shahzad Ali Shahid Chatha; Muhammad Asgher; Rabbia Asgher; Abdullah Ijaz Hussain; Yasir Iqbal; Syed Makhdoom Hussain; Muhammad Bilal; Faizan Saleem; Hafiz M.N. Iqbal (Science of The Total Environment, 2026)

Spatiotemporal reorganization of coastal wetlands along the Pakistan coast under climatic variability and human modification (2019-2024) - Muhammad Asgher Ali; Yaseen Laghari; Zhenguo Niu; Qingyu Li (Estuarine, Coastal and Shelf Science, 2026)

Variation in Ectotherm Thermal Tolerances With Elevation and Temperature Across Biological Scales - Imran Khaliq; Edward Lavender; Haseeb Kamran; Muhammad Junaid Shahid; Muhammad Sheraz; Muhammad Awais; Mehtab Shabir; Muhammad Yasir; Abdul Hameed; Muhammad Asgher; Abdul Rehman; Maria Riaz; et al. (Global Ecology and Biogeography, 2025)
Aim Variation in thermal tolerances along environmental gradients is assumed to follow similar patterns across different biological scales, including within and between species, and across communities. However, this assumption has yet to be tested using comprehensive datasets collected through standardised methodologies. Location Southern Asia. Time Period 2017–2019. Major Taxa Studied Ants, beetles, grasshoppers, and spiders. Methods We quantified the associations between thermal tolerance traits and elevation or temperature at three biological scales (community, broad taxonomic group, and species) along two distinct elevational transects in Southern Asia. In total, we measured thermal tolerances of over 15,000 individuals from 114 arthropod species belonging to four invertebrate taxa (ants, beetles, grasshoppers, and spiders). We compared the relationships at each scale using mixed‐effects models. Results At the community scale, across all individuals of all species, we found a consistent decline in the values of three thermal tolerance traits (upper tolerance, lower tolerance, and tolerance breadth) with elevation along the Himalayan transect but an increase in the values of upper and lower tolerance along the Sulaiman transect. The relationships of thermal tolerance traits and elevation/temperature varied among the groups and species between the Himalayan and Sulaiman transects. This suggests that factors beyond elevation, including vegetation composition, microclimate, landscape features, and local adaptation, drive observed variation in thermal tolerance traits among and within species. Conclusion Our study highlights the interplay between thermal physiology and the environment across different habitats and biological scales. Our findings indicate that predicting biodiversity responses to environmental change based on thermal tolerance–environment relationships requires careful consideration of group‐ and species‐level variation. This is essential for improving the accuracy of climate change impact assessments on biodiversity.

Wetland dynamics in the Indus River Delta: A Sentinel-2 and machine learning approach - Yaseen Laghari; Zhenguo Niu; Shah Jahan Leghari; Muhammad Asgher Ali; Qingyu Li; Junkai Shi (Journal of Environmental Management, 2025)

Innovative Nanotechnology and Molecular Probes for Real-time Monitoring and Therapeutic Modulation of Pyroptosis in Cancer and Inflammatory Diseases - Wajahat Ali; Zainab Saba; Muhammad Saqib; Shabana Batool; Awais; Fatima Rahman; Ali Asgher Shuja; Junaid Abid; Seema Batool; Kulsoom; Mukhayya Ruzieva; Murodjon Yaxshimuratov; et al. (Cell Biochemistry and Biophysics, 2025)

Functionalized graphene oxide-zinc oxide hybrid material and its deployment for adsorptive removal of levofloxacin from aqueous media - Nimra Ismail; Muhammad Imran; Muhammad Ramzan; Ayesha Anwar; Ibrahim A. Alsafari; Muhammad Asgher; Hafiz M.N. Iqbal (Environmental Research, 2023)

Exopolysaccharides production from marine Bacillus strains and their antioxidant and bio-flocculant capacities - Nimrah Khalid; Muhammad Asgher; Fatma Hussain; Javed Iqbal (Archives of Microbiology, 2022)

Microbial exopolysaccharide-based nano-carriers with unique multi-functionalities for biomedical sectors - Muhammad Asgher; Sarmad Ahmad Qamar; Hafiz M. N. Iqbal (Biologia, 2021)

Optimization of biosurfactant production from chemically mutated strain of Bacillus subtilis using waste automobile oil as low-cost substrate - Muhammad Asgher; Mariam Afzal; Sarmad Ahmad Qamar; Nimrah Khalid (Environmental Sustainability, 2020)

Enzyme-based solutions for textile processing and dye contaminant biodegradation—a review - Shahzad Ali Shahid Chatha; Muhammad Asgher; Hafiz M. N. Iqbal (Environmental Science and Pollution Research, 2017)

Bio-based degradation of emerging endocrine-disrupting and dye-based pollutants using cross-linked enzyme aggregates - Muhammad Bilal; Muhammad Asgher; Hafiz M. N. Iqbal; Hongbo Hu; Xuehong Zhang (Environmental Science and Pollution Research, 2017)

Degradation and Mineralization of Azo Dye Reactive Blue 222 by Sequential Photo-Fenton’s Oxidation Followed by Aerobic Biological Treatment Using White Rot Fungi - Shumaila Kiran; Shaukat Ali; Muhammad Asgher (Bulletin of Environmental Contamination and Toxicology, 2013)

Recent developments in biodegradation of industrial pollutants by white rot fungi and their enzyme system - Muhammad Asgher; Haq Nawaz Bhatti; Muhammad Ashraf; Raymond L. Legge (Biodegradation, 2008)

Decolorization potential of mixed microbial consortia for reactive and disperse textile dyestuffs - Muhammad Asgher; H. N. Bhatti; S. A. H. Shah; M. Javaid Asad; R. L. Legge (Biodegradation, 2007)

Hyperactivation and thermostabilization of Phanerochaete chrysosporium lignin peroxidase by immobilization in xerogels - Muhammad Asgher; M. Javaid Asad; Haq Nawaz Bhatti; Raymond L. Legge (World Journal of Microbiology and Biotechnology, 2007)

Purification and Characterization of a Xylanase Produced by Chaetomium thermophile NIBGE - Farooq Latif; Muhammad Asgher; Rabia Saleem; Ahmed Akrem; R. L. Legge (World Journal of Microbiology and Biotechnology, 2006)